Combined numerical and experimental approach to determine numerical model of abdominal scaffold. Issue 11 (15th August 2022) - Tomaszewska, Agnieszka; Reznikov, Daniil
Abstract: A proper junction of the prosthesis and the abdominal wall is important in successful hernia repair. The number of tacks should be balanced to assure appropriate mesh fixation and not to induce post-operative pain. Numerical simulations help to find this balance. The study is aimed at creating a proper numerical model of a knitted surgical mesh subjected to boundary conditions and load occurring in the abdominal cavity. Continuous, anisotropic constitutive relation is considered to reflect the mesh behaviour. Different sets of material law parameters are determined on the basis of different bi-axial tests setups. Force- and displacement-controlled tests with different ratios are considered. Consequently, some numerical model variants are obtained featuring various reaction distributions in the scaffold fixation points. The proper variant is selected based on comparison of the position of maximal reaction force in the numerical model and in the reference physical model of operated hernia. Force-driven tests have shown anisotropic mesh behaviour, while equibiaxial displacement-driven test has demonstrated reduced anisotropic response. Within seven scenarios of constitutive parameters identification (based on single or combined experimental data), the equibiaxial force-controlled test appeared to produce the most relevant model to follow the prosthesis behaviour under pressure. The position of maximal reaction force in such model is similar to obtained in the physical hernia model. The equibiaxial force-driven test provides most suitable data for Gasser-Ogden-Holzapfel constitutive model identification of a considered surgical mesh to be used to model the mesh under pressure.